TOXICOGENETIC AND BIOCHEMICAL EFFECTS OF WATER AND SEDIMENT FROM A COASTAL LAGOON (ES/BRAZIL) ASSESSED WITH ALLIUM CEPA - Santos, Kristian Rodolfo; Galter, Iasmini Nicoli; dos Santos, Sara Nascimento; Aragão, Francielen Barroso; Boeque Lascola, Mylena; Souza, Iara da Costa; Almeida, Stéfano Zorzal; Monferrán, Magdalena Victoria; Wunderlin, Daniel Alberto; Fernandes, Marisa Narciso; Matsumoto, Silvia Tamie (Acta Biologica Brasiliensia, 2025)
The occurrence of metals in aquatic environments is natural and essential for various metabolic functions. However, when in excess due to contamination, these elements can cause toxic effects. The Mãe-Bá Lagoon, located between the municipalities of Guarapari and Anchieta, in Espírito Santo, has suffered anthropogenic impacts since the 1970s, with the closure of its connection to the sea and the installation of a reservoir for processing iron ore. The aim of this study was to evaluate the toxicogenetic, biochemical, and metal responses of Allium cepa exposed to water, elutriate, and solubilized sediment samples collected at three stations in Mãe-Bá Lagoon (ES, Brazil). The results revealed phytotoxicity at the three stations in the first campaign; cytotoxicity in the elutriate from station 1 and in the solubilized water from stations 2 and 3 in the second campaign; genotoxicity in the water from station 1 in the first campaign and in the solubilized water from stations 2 and 3 in the second campaign; as well as mutagenicity in several samples. Alterations were also observed in antioxidant defense enzymes, such as lipid peroxidation and glutathione S-transferase, as well as the accumulation of metals in the roots of the exposed seeds, indicating a potential risk to the local biota.